2004
DOI: 10.1038/sj.bjc.6602088
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of human papillomavirus 16 serological conversion and persistence in a population-based cohort of 10 000 women in Costa Rica

Abstract: Determinants of human papillomavirus (HPV)-16 serological conversion and persistence were assessed in a population-based cohort of 10 049 women in Guanacaste, Costa Rica. Serologic responses to HPV-16 were measured in 7986 women by VLP-based enzymelinked immunosorbent assay at both study enrolment (1993/94) and at 5 -7 years of follow-up. Seropositive women were defined as X5 standard deviations above the mean optical density obtained for studied virgins at enrolment (n ¼ 573). Seroconnversion (n ¼ 409), persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
2
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 29 publications
5
56
2
3
Order By: Relevance
“…These factors were also reported by Wang et al (2004) as the only predictors of HPV 16 seroconversion. In contrast to these, the only predictors of LR-HPV conversion were status of employment and anal sex.…”
Section: S Syrjä Nen and Others 1522mentioning
confidence: 85%
“…These factors were also reported by Wang et al (2004) as the only predictors of HPV 16 seroconversion. In contrast to these, the only predictors of LR-HPV conversion were status of employment and anal sex.…”
Section: S Syrjä Nen and Others 1522mentioning
confidence: 85%
“…The Guanacaste cohort study showed that serologic status was a dynamic result of seroconversion and clearance (48). Only 55% of 1,216 women HPV16-seropositive at enrollment remained positive at 5 to 7 years of follow-up, while 6% seroconverted.…”
Section: Discussionmentioning
confidence: 99%
“…With a few exceptions [18,20], these assays have not been directly compared. L1 VLP-based ELISA has been extensively used in studies of HPV epidemiology and vaccinology [6,19,[21][22][23][24]. Generally, ELISAs are a fast and highly reproducible method for quantifying humoral responses against specific viral antigens, but the quantitation is independent of neutralizing activity.…”
Section: Introductionmentioning
confidence: 99%